The Struggle For Female Autonomy In Leila Slimani’s In The Country Of Others - Amelia Yuli Astuti; Amelia Zulfi Amelia Zulfi (Fakultas Sastra Universitas Ekasakti, 2026)
This research examines the struggle of the character Mathilde in asserting her right to speak and the forms of resistance she shows against the patriarchal structure within her husband's family in Morocco. The research also highlights Mathilde’s independent attitude, demonstrated through her refusal to submit to her husband's authority and her ability to make her own decisions. This research uses a qualitative approach with content analysis as the method, in which the researcher analyzes written sources such as novels, articles, and relevant books. The main focus of this study is to identify and classify the forms of Mathilde’s resistance against patriarchy, as well as actions that reflect her independence. The analysis reveals 9 data points representing Mathilde’s resistance to patriarchal structures and 7 data points showing her independent behavior in the novel In the Country of Others by Leïla Slimani. This study applies feminist theories by Tong (2014) and Djajanegara (2000) as the theoretical foundation to identify and explain the issues being analyzed. Data were obtained from written sources such as books, articles, and literary texts, and then analyzed to explore gender dynamics and women’s struggles within the context of patriarchal and colonial cultures. This research contributes to the understanding of how female representation in postcolonial literature reflects complex social realities, and opens up discussion about the importance of women’s voices and independence in facing oppressive systems.